Corporate governance, professional regulation and audit quality / Alan Kilgore - Kilgore, Alan (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
The recent spate of corporate failures around the world has attracted considerable attention from corporate regulators and professional bodies. Although corporate failures are not new, what is of increasing concern to stakeholders is the unexpected collapse of many apparently financially robust companies. One of the many victims of these collapses has been the reputation of audit firms, the audit process, and the accounting profession generally. The purpose of this paper is to first, outline the importance of audit quality in the operation of capital markets. Second, to place the issue of audit quality in context. Third, outline and synthesize prior research on audit quality and finally, to consider the responses that regulators and the profession can and should consider based on the available empirical evidence.